Medicare Claims Paid by the Federal Black Lung Benefits Program: US Medicare Beneficiaries, 1999 to 2016. Issue 12 (December 2019) - Kurth, Laura; Casey, Megan; Schleiff, Patricia; Halldin, Cara; Mazurek, Jacek; Blackley, David
Abstract : Objective: To establish the burden of totally disabling respiratory impairment among coal miners, we identified the healthcare utilization and cost for Medicare claims where the Federal Black Lung Program (FBLP) was the primary payer. Methods: We extracted FBLP claims from 1999 to 2016 institutional Medicare data along with beneficiary, comorbidity, and claim cost information. Healthcare utilization was evaluated and compared to the 2016 Medicare population. Results: The FBLP was the primary payer on 75, 690 claims from 19, 700 beneficiaries and paid an increasing percentage of the total paid to providers annually. Claims decreased from 1999 to 2016 but cost per claim increased. Beneficiaries were hospitalized and visited the ER for respiratory and cardiovascular conditions. Conclusions: Medicare beneficiaries with FBLP primary payer claims have higher healthcare utilization and comorbidities compared with Medicare enrollees, indicative of increased financial and healthcare burden.